Refining Diagnosis of Schistosoma haematobium Infections: Antigen and Antibody Detection in Urine - de Dood, Claudia J.; Hoekstra, Pytsje T.; Mngara, Julius; Kalluvya, Samuel E.; van Dam, Govert J.; Downs, Jennifer A.; Corstjens, Paul L. A. M. (Frontiers in Immunology, 2018)
Background: Traditional microscopic examination of urine or stool for schistosome eggs lacks sensitivity compared to measurement of schistosome worm-derived circulating antigens in serum or urine. The ease and non-invasiveness of urine collection makes it an ideal sample for schistosome antigen detection. In this study several user-friendly, lateral-flow (LF) based urine assays were evaluated against a composite reference that defined infection as detection of either eggs in urine or anodic antigen in serum. Method: In a Tanzanian population with a S. haematobium prevalence of 40-50% (S. mansoni prevalence <2%), clinical samples from 44 women aged 18 to 35 years were analyzed for Schistosoma infection. Urine and stool samples were examined microscopically for eggs, and serum samples were analyzed for the presence of the anodic antigen. Urine were further subjected to a set of LF assays detecting (circulating) anodic (CAA) and cathodic antigen (CCA) as well as antibodies against soluble egg antigens (SEA) and crude cercarial antigen preparation (SCAP). Results: The urine LF anodic antigen assay utilizing luminescent upconverting reporter particles (UCP) confirmed its increased sensitivity when performed with larger sample volume. Qualitatively, the anodic antigen assay performed on 250 L urine matched the performance of the standard anodic antigen assay performed on 20 L serum. However, the ratio of anodic antigen levels in urine versus serum of individual patients varied with absolute levels always higher in serum. The 10 L urine UCP-LF cathodic antigen assay correlated with the commercially available urine POC-CCA (40 L) test, while conferring better sensitivity with a quantitative result. Urinary antibodies against SEA and SCAP overlap and correlate with the presence of urinary egg and serum anodic antigen levels. Conclusions: The UCP-LF anodic antigen assay using 250 L of urine is an expedient user-friendly assay and a suitable non-invasive alternative to serum-based antigen testing and urinary egg detection. Individual biological differences in the clearance process of the circulating antigens are thought to explain the observed high variation in the type and level of antigen (anodic or cathodic) measured in urine or serum. Simultaneous detection of anodic and cathodic antigen may be considered to further increase accuracy.